Prove the above following integral




Prove the above following integral


2 Answers

Ramesh V
70 Points
13 years ago

put t =ex/(x2+1)1/2

     dt = 1/(x2+1)*(ex.(x2+1)1/2 - ex.x/(x2+1)1/2)

         = ex(x2-x+1)/(x2+1)

I = integral of ( t.dt)

  =t2/2 + C

  = e2x/2.(x2+1)   + C


Please feel free to post as many doubts on our disucssion forum as you can. If you find any question difficult to understand - post it here and we will get you the answer and detailed solution very quickly.We are all IITians and here to help you in your IIT JEE preparation. All the best.

IIT Kgp - 05 batch

vikas askiitian expert
509 Points
12 years ago

integral of e^x.(x^2-x+1)/(x^2+1)3/2


above expression can be rewritten as e^x.([x^2+1]/[x^2+1]^3/2 + [-x/(x^2+1)3/2])


integral of e^x(fx + dfx/dx) =e^x.fx +c


  so ans is e^x.1/(x^2+1)^1/2 


Think You Can Provide A Better Answer ?